Fast neutron radiography and tomography at a 10 MW research reactor beamline. (January 2017) - Zboray, R.; Adams, R.; Kis, Z.
Abstract: Fast neutron imaging was performed using a beamline of the 10 MW research reactor of the Budapest Neutron Centre, Hungary. A simple, low-cost 2D area detector has been used featuring a 8 mm thick BC400 plastic scintillator converter screen and a CCD camera. A spatial resolution of around 1.3 mm has been achieved. Typically 10 min long exposures were needed to obtain reasonable quality radiographic images. For tomographic imaging typically several hours of acquisition were needed to obtain reasonable quality on non-symmetric and larger (e.g. 10 × 10 × 10 cm 3 ) objects. Due to the presence of a significant gamma background at the experimental position, massive (30 cm thick) lead shielding and filtering was applied to the beam. The gamma contribution was mostly baseline independent of the object imaged and therefore could be subtracted, whereas the direct gamma contribution from the beam to the imaging detector signal is estimated to be less than 1%. Abstract : Highlights: Fast neutron imaging is performed at a 10-MW research reactor beamline. A low-cost, 2D imaging detector featuring plastic scintillator converter has been used. Spatial resolution of around 1.3 mm is achieved in imaging robust objects. Exposure times of several minutes for radiography, and several hours for tomography, are needed for reasonable image quality. Gamma contribution to the images is shown to be negligible.